A reappraisal of the generic status of Gastrocotyle, Hormuzakia and Phyllocara(Boraginaceae) in the light of micromorphological and karyological evidence - Bigazzi, M.; Selvi, F.; Fiorini, G. (Edinburgh Journal of Botany, 1999)
The results of karyological analyses and SEM micromorphological observations on vegetative and reproductive structures of the critical genera Gastrocotyle, Hormuzakia and Phyllocara (Boraginaceae: Boragineae) are presented and discussed in relation to their taxonomic position within the tribe. Each of these monotypic genera is characterized by distinctive features in stigma morphology, papillar pattern, structure of faucal scales, development of the hairy annulus at the base of the corolla tube and ornamentation of the mericarp coat surface. G. hispida and H. aggregata showed 2n = 16 and complements of medium-sized and very large chromosomes, respectively. P. aucheri was characterized by a tetraploid set of 32 chromosomes including a group similar to those of Anchusa and a group closer to those of Nonea in terms of size and centromcric position. This species could have an allopolyploid origin, resulting from the hybridization of members of these two genera. Along with distinctive traits in inflorescence structure, fruit shape and pollen morphology, karyological and micromorphological characters determine sharp phenetic discontinuities from Anchusa, from which these plants should be kept generically separated. At the same time, the presence of relevant autapomorphies in each of the three genera prevents them from being merged in a single genus.